Long and winding road toward change in teachers’ goals and orientations in the instructional lab - Smadar Levy; Adi Noga; Edit Yerushalmi (Physical Review Physics Education Research)
Teachers’ goals and orientations underlie their instructional decision making and can make the difference between “talking the talk” and “walking the walk” when trying to change lab instruction. Schoenfeld’s Resources, Orientations, and Goals (ROG) framework was employed to shed light on the challenges involved in a reform in lab instruction that aims to grant students more agency in experimental research practices. We focus on high school physics teachers engaged in a professional development process as members of a national network of Professional Learning Communities (PLCs, N≈275 participants). One of the annual themes in the PLCs addressed lab instruction. The teachers were involved in: (a) experiencing, as learners, Deliberation Labs designed to reform lab instruction while taking into consideration the widespread constraints faced by high school teachers; and (b) engaging in collaborative reflection on their classroom experiences to encourage them to rethink their ROGs. The data were gathered from two professional development sequences held during the 2020 and 2022 school years that differed in the structuring of collaborative reflection. To achieve a large-scale portrayal of teachers’ goals and orientations toward integrating experimental research practices in the instructional lab, we analyzed surveys administered in the PLCs. The survey results highlighted two main orientations that interfered when implementing the Deliberation Labs: the “lab serving theory” orientation and the “restricting agency” orientation. To better understand the processes of change in teachers’ ROGs, we present two case studies that were involved in the structured collaborative reflection on practice. They deal with experienced PLC teacher-leaders who were motivated to try out the Deliberation Labs in their classrooms. The analysis shows how they interpreted their experiences in ways that align with the lab serves theory orientation, thus undermining the goals that the Deliberation Labs were designed to achieve. These results highlight the winding road to change in teachers’ ROGs and emphasize the need to support them in resolving conflicting goals and orientations. They also raise dilemmas regarding the nature of feasible yet effective professional development programs that can lead to large-scale change.